Building capacity for bioinformatics - Latin America. Project profile. - International Potato Center (International Potato Center, 2019)
Data-driven biology could have a major impact on health, agriculture, and environmental management, but Latin American scientist have yet to fully benefit from this new approach. The ‘CABANA’ project aims to promote the use of bioinformatics in lead institutions, which will form hubs for wider dissemination throughout the continent.